FAKTOR YANG MEMPENGARUHI PERKEMBANGAN INDUSTRI KREATIF SUBSEKTOR SENI KRIYA DI BANJARMASIN - ISMAYANTI ISMAYANTI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This research is conducted to know the factors that influence the development of creative industries craft sub-sector in Banjarmasin and How the condition of SDA, HR, technology, Marketing and Capital, And how its influence and what the right development strategy what is the right developmentThe data used is Primary data obtained through questionnaire, interviews, and observations on the creative industries sub-sector craft art in Banjarmasin by using descriptive analysis and SWOT analysis.The results showed that the condition of natural resources and human resources is sufficient but the quality is still low, then the technology used is relatively traditional, while the marketing conditions are not broad, then the capital used is still small because it is only limited to own capital and family. Factors affecting the development of creative industries craft sub-sector in Banjarmasin are SDA, SDM, technology, Marketing and capital are interrelated and each other. Strategy that can be used based on SWOT is horizontal strategy which means that the creative industry should be more expansive in its business.Keywords: craft art sub-sector in creative industry, human resources, natural resources, marketing, technology, capital, development strategy, SWOT analysis